STYLISTIC ANALYSIS OF SURAKH AL-QUBUR: A SHORT STORY BY KAHLIL GIBRAN / ANALISIS STILISTIKA CERPEN SURAKH AL-QUBUR KARYA KAHLIL GIBRAN - M. Mahbub Junaidi (IAIN Batusangkar, Indonesia, 2021)
This study aims to reveal the stylistic used in a short story written by Kahlil Gibran entitled â€œSurakh al-Quburâ€ and also to describe the effect of it toward meaning. This is a descriptive qualitative research that used stylistic analysis to show the aesthetics side found in the short story. Based on data analysis, it was found that there are five categories of language styles in short story Surakh al-Qubur, they are: first, lexical (synonym and typical words); second, grammatical (verb and noun); third, rhetorical (alliteration, asyndeton, assonance, chiasmus, polysyndeton, and hyperbole) and figure of speech (metaphor, personification, simile, and eponym); fourth, cohesion and connectors such as al-wawu, al-faâ€™u, tsumma, au, and am; and fifth, character speech that can be analyzed using narration and dialogue. The influence of stylistic on meaning is that readers get the information directly or indirectly, feels sadness, gives advice, gets a picture of injustice, makes readers curious and more focused.